CRETACEOUS DEFORMATION, CHEGITUN RIVER AREA, CHUKOTKA PENINSULA, RUSSIA: IMPLICATIONS FOR THE TECTONIC EVOLUTION OF THE BERING STRAIT REGION - Toro J.; Amato J.M.; Natal'in B. (My University, 2003)
The Koolen metamorphic dome of Chukotka Peninsula has been interpreted as a mid-Cretaceous extensional core complex. On the NW flank of the dome, three lithotectonic units are exposed: (1) High-Grade unit, composed of sillimanite-grade rocks; (2) Tanatap unit, composed of polydeformed greenschist-grade phyllites and marbles; (3) Chegitun unit composed of unmetamorphosed early Paleozoic limestones. Four Early Cretaceous to Tertiary deformational events are documented. D1 is attributed to the collisional closure of the South Anyui suture. The 40Ar/39Ar ages from the Tanatap unit constrain this event at 117–124 Ma. Relict kyanite-bearing assemblages in the High-Grade unit probably formed during this event under moderately high pressure conditions. D2 is related to extensional deformation in the Koolen dome. In the High-Grade unit, sillimanite-grade metamorphism was followed by rapid cooling and exhumation at 109–104 Ma. In the Tanatap unit, early fabrics underwent isoclinal folding, and a new cleavage (S2t) was developed. The kinematics of the High-Grade unit indicates ductile deformation by top-to-the-south shear, as is the case in the dome core. This suggests that the Koolen dome is a unidirectional core complex formed by south directed extension. We believe collapse of overthickened crust caused extension in the Koolen dome. The crust was thickened during Early Cretaceous collision and during subsequent oroclinal bending of the structures in the Bering Strait region. The youngest structures in the Chegitun Valley are NW striking normal faults kinematically linked to NE striking right-lateral strike-slip faults. They are probably the continuation of structures found offshore in the Hope Basin.
Keywords: Koolen Dome; extension; Arctic; thermochronology; core complex; Mesozoic::Cretaceous; Мезозой::Меловая